2012
DOI: 10.1155/2012/635314
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Complications following Cytoreductive Surgery and Perioperative Chemotherapy in 147 Consecutive Patients

Abstract: Cytoreductive surgery (CRS) with hyperthermic perioperative chemotherapy (HIPEC) has become a treatment option for selected patients with peritoneal metastases (PMs) from gastrointestinal malignancies. The purpose of this study is to evaluate our most recent data regarding pulmonary complications (respiratory distress, pleural effusion, and pneumonia) and attempt to identify risk factors associated with this management plan. This study includes the most recent 4-year experience with appendiceal and colorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Several studies have reported the incidence of grade 3/4 pulmonary complications to be in the range of 10-16 % [15,[22][23][24]. As expected, peritonectomy of abdominal diaphragmatic surfaces significantly increases post-operative pleural effusions, particularly in absence of systematic thoracic drainage [25,26].…”
Section: Pulmonary Complicationsmentioning
confidence: 82%
See 1 more Smart Citation
“…Several studies have reported the incidence of grade 3/4 pulmonary complications to be in the range of 10-16 % [15,[22][23][24]. As expected, peritonectomy of abdominal diaphragmatic surfaces significantly increases post-operative pleural effusions, particularly in absence of systematic thoracic drainage [25,26].…”
Section: Pulmonary Complicationsmentioning
confidence: 82%
“…As expected, peritonectomy of abdominal diaphragmatic surfaces significantly increases post-operative pleural effusions, particularly in absence of systematic thoracic drainage [25,26]. However, this strategy can reduce but not abolish intrinsic risk of pleural effusion, which remains the second most common pulmonary complications [22].…”
Section: Pulmonary Complicationsmentioning
confidence: 88%
“…Regarding the conventional coagulation tests previous studies on HIPEC procedure have demonstrated hypocoagulation with possible development of DIC during surgery and the perioperative period [24][25][26][27]. We used P-TT, APTT and platelet count as conventional testing for blood coagulation during CRS.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to us many studies have reported that respiratory complications like effusion, hypoxia, atelectasis and adult respiratory distress syndrome (ARDS) are the second most common adverse events after abdominal complications. Plueral effusion is common to occur after this procedure which could be reactive or due to opening of plueral space during sub-diaphragmatic peritoneal stripping [17]. To circumvent this issue we prophylactically inserted intercostal drain tube whenever diaphragmatic stripping was done.…”
Section: Discussionmentioning
confidence: 99%